Peran Literasi Digital Dalam Menangkal Hoaks Keagamaan Di Media Sosial Pada Remaja - Arentania, Mutia Nurul; Afriliani, Cindy; Razzaq, Abdur; Nugraha, Muhamad Yudistira (NAAFI: JURNAL ILMIAH MAHASISWA, 2025)
Teenagers are a generation that is synonymous with always being connected to digital technology in their daily lives. This causes teenagers to actively use the internet. Moreover, teenagers are vulnerable to negative elements including not being able to provide verification; being quickly influenced by the application of hoaxes. That is why digital literacy should not be completely ignored. In fact, one of the more important functions of digital literacy is to direct young people to be more sensitive in doing minimal detection of some signs of hoax news that have been circulating on the internet. This study aims to explain digital literacy as a way to tackle fake news or hoaxes. The method used in this research is descriptive qualitative. The types of data collected through interviews, observation, and documentation. The selection of interview guests was carried out purposively, and the number of sources was 9 data. The results of the research that have been carried out also show that digital literacy learning has been implemented at Fitra Abdi Palembang Junior High School directly.Digital literacy is very important to help adolescents understand that they must act smart and wise when using digital media, especially social media. To avoid the negative impact of fake news, digital literacy is essential for using social media along with the intelligence to assess information carefully and critically.